The Status of research for the management of the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) in Sub-Saharan Africa - Bakaze, Elyeza; Tinzaara, William; Gold, Cliford S.; Kubiriba, Jerome (European Open Science Publishing, 2022)
The banana weevil Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae] is a major pest of East African highland bananas and plantains. Its larvae bore in corm tissue damaging the root system, disrupting nutrient and water uptake, compromising plant anchorage, reducing yield, and shortening plantation life. Yield losses in bananas and plantains may exceed 50%. Available technologies for the management of the pest include cultural control, biological control, and chemical control. These methods may be costly, labor intensive, or ecologically unsustainable. Such effects, together with developed pesticide resistance, have led to various efforts searching for sustainable alternatives. To achieve this, there is a need to understand the biology of the pest and the currently available management options which includes use of cultural practices, resistant banana varieties, biological and microbial control, pheromone trapping and chemical and botanical insecticides. This article reviews the research status concerning C. sordidus biology, distribution, management options, including current innovations such as genome editing, and suggests future research directions for the management of the pest. Research findings suggest that no single control strategy will provide complete control. The integration of appropriate conventional C. sordidus management options with genetic engineering and other ecologically friendly methods such as use of botanicals and infochemicals will manage the pest and ustainably increase banana production.